Trypanosoma cruzi trans-sialidase initiates a program independent of the transcription factors RORγt and Ahr that leads to IL-17 production by activated B cells - Bermejo, Daniela Andrea (2013)
Here we identified B cells as a major source of rapid, innate-like production of interleukin 17 (IL-17) in vivo in response to infection with Trypanosoma cruzi. IL-17+ B cells had a plasmablast phenotype, outnumbered cells of the TH17 subset of helper T cells and were required for an optimal response to this pathogen. With both mouse and human primary B cells, we found that exposure to parasite-derived trans-sialidase in vitro was sufficient to trigger modification of the cell-surface mucin CD45, which led to signaling dependent on the kinase Btk and production of IL-17A or IL-17F via a transcriptional program independent of the transcription factors RORγt and Ahr. Our combined data suggest that the generation of IL-17+ B cells may be a previously unappreciated feature of innate immune responses required for pathogen control or IL-17-mediated autoimmunity.